KESADARAN HUKUM MASYARAKAT DALAM BERLALU LINTAS DI KEPULAUAN MERANTI - RUBA’I '; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Problem level of public awareness in traffic in the islands Meranti, although the handling of law enforcement against violations of the motor vehicle in the city of existing Selatpanjang based on Law No. 22 of 2009 on Traffic and Road Transportation, but many indicators against people who are not prioritizing safety needs as a rider who always ignore traffic rules. This is because the habits of people who are not exactly in a motorcycle. The purpose of writing this thesis namely, first, to determine the level of public awareness in traffic. Second, to determine the constraints faced by the police, Third, how is the effort made by the police to address the low level of public awareness of traffic.This type of research that will be used is a sociological law research, because in this study the authors directly conduct research on locations or places studied in order to give a complete and clear picture of the problems examined. This research was conducted the islands meranti, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary, secondary and terser, data collection techniques in this study by observation, interview and literature study.From the research there are three basic problems that can be inferred. First, the level of public awareness in traffic the islands Meranti are so low, based on the rules of traffic laws and regulations. Second, the constraints faced by the police handling of public awareness in traffic, based on Article 264 and 281 in conjunction with Article 77 paragraph (1) of Law No. 22 Year 2009 regarding Traffic and Road Transportation. The obstacles encountered by the police are the people who do not understand and ignore traffic rules. The third attempt was made by the police to deal with the low level of public awareness that is done, deterrence which is the Police high command positions. Suggestions writer, first giving guidance and education so the activities will go smoothly throughout elements of society both organized and unorganized, so the program more effective. Secondly, a need for improvement in terms of supervision so the rule is run with the maximum and running smoothly, the third, the sound in the form of delivery at one of the intersections of the memorial motorcycle driving rules as set out in the applicable legislation.Keywords: Level of Legal Awareness Society